2022
DOI: 10.1016/j.pdpdt.2022.102726
|View full text |Cite
|
Sign up to set email alerts
|

Retinal findings of COVID-19 patients using ocular coherence tomography angiography two to three months after infection

Abstract: PURPOSE The aim of this study was to evaluate the ocular disorders in COVID-19 patients, two to three months after infection. METHODS In this cross-sectional, historically controlled study, fifty-one COVID-19 patients were compared with thirty-seven age, and gender-matched healthy individuals. After complete ophthalmological examination, all participants underwent peripapillary and macular optical coherence tomography, and optical coherence tomography angiography (OCTA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Leave one out sensitivity analysis showed that when the study of Naderi Beni et al [22] was excluded from the analysis of the whole image VD at SCP, there was a statistically significant reduced VD in the COVID-19 recovered group compared to healthy controls (SMD=-0.37, 95% CI=-0.68 to -0.05, p=0.02, I 2 =76%). In the DCP foveal VD, when the studies of Cennamo et al, Abrishami et al, Bilbao-Malave et al and Erogul et al were excluded from the analyses, the results were no longer statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leave one out sensitivity analysis showed that when the study of Naderi Beni et al [22] was excluded from the analysis of the whole image VD at SCP, there was a statistically significant reduced VD in the COVID-19 recovered group compared to healthy controls (SMD=-0.37, 95% CI=-0.68 to -0.05, p=0.02, I 2 =76%). In the DCP foveal VD, when the studies of Cennamo et al, Abrishami et al, Bilbao-Malave et al and Erogul et al were excluded from the analyses, the results were no longer statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic database search identified 754 articles. After screening of all titles and abstracts of potentially relevant articles, a total of 12 studies met the inclusion criteria [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ( Figure 1 ). The study characteristics and Newcastle Ottawa scores of the included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The ocular manifestations of COVID-19 infection include episcleritis, uveitis, conjunctivitis, retinal vascular changes such as cotton wool spots, retinal hemorrhages, dilated veins, and tortuous vessels, ocular motility defect, optic neuritis, cranial nerve palsies, acute dacryoadenitis, ocular myasthenia gravis, and epiphora [11] , [12] .…”
Section: Discussionmentioning
confidence: 99%
“…89 A more recent study also demonstrated the same findings. 90 The results suggest that some of the patients were recovering from occult intracranial hypertension or disc inflammation. Interestingly, patients who had experienced anosmia and ageusia showed higher thicknesses than patients without these symptoms, suggesting an increased risk of CNS infiltration in patients with involvement of the olfactory epithelium.…”
Section: Optical Coherence Tomography and Covid-19mentioning
confidence: 93%